1, 4-Bis (β-Pyridyl-2-Vinyl) Benzene (P2VB) and 2, 5-Distyryl-pyrazine (DSP) as Blue Laser Dyes. Issue 4 (1985) - Ebeid, E. M.; Sabry, M. M. F.; El-Daly, S. A.
Abstract : Solutions of P2VB and DSP in dimethyl-sulphoxide (DMSO) of concentration ca. 10 –3 M/l act as laser dyes on pumping with nitrogen laser. P2VB and DSP are lasing in the ranges 390–440 nm (λmax = 416 nm) and 435–465 nm (λmax = 447 nm) respectively. An equimolar mixture of P2VB and DSP behaves as an energy transfer dye laser (ETDL) and is lasing in the range 429–455 nm (λmax = 438 nm). Such ETDL system obeys a long range coulombic energy transfer mechanism with a critical transfer distance R 0 = 7.5 nm. The fluorescence quantum yields of both dyes have been measured, and in DMSOφ f = 0.46 and 0.35 for P2VB and DSP respectively. Both dyes show a remarkable photostability upon nitrogen laser excitation. This has been attributed to the role of the 337 nm light in inducing a back photo-chemical reaction of the initially formed photoproducts consisting mainly of photo-oligomers and cis -photoisomers.